Resilient Performance of Self-Centering Hybrid Rocking Columns: Theory, Experiment, and Numerical Simulation - Shi Yan; Tao Wang; Xing Su (Advances in Civil Engineering)
A novel self-centering hybrid rocking column (HRC) with a replaceable soft steel energy dissipator (RED) is proposed to solve the issue of traditional frame structures being vulnerable to damage during earthquakes and difficult rehabilitation after. The resilient performance of the proposed RED-HRC was investigated by using theoretical, experimental, and numerical methods. The yield states of the designed RED are taken as the control points to establish theoretically the corresponding relationship f (M, θ) between the overturning moment M and the rotation angle θ of the RED-HRC. In addition, a group of RED-HRC specimens were tested under pseudo static loading to investigate the resilient performance by considering the main influencing factors of the cross-sectional area of the prestressed unbonded tendons, the initial value of the prestressing force, the axial compression ratio of HRCs, and the thickness of the RED. Moreover, a finite element model (FEM) validated by the experimental data was established by using the ABAQUS platform to further study the resilience of the proposed RED-HRCs, focusing on the energy dissipating efficiency of the RED. The design method and process for the RED-HRC were finally developed. A typical hysteretic response with “double-flag shape” characteristics was obtained. These results show that the proposed RED-HRC has excellent resilient performances of good energy dissipation capacity, strong self-centering ability, and high strength and stiffness, realizing the goal of low damage level during the earthquake and quick rehabilitation after.